The savage garden - Mills, Mark, 1963-; Harper Collins (London : Harper Collins, 2007)
Cambridge art history major Adam Strickland travels to Italy during the summer of 1958 to research a famous sixteenth-century garden, and is drawn into the intrigue of two mysterious deaths that occured four hundred years apart.
Adult
Keywords: College students -- Fiction; College teachers -- Fiction; Colleges and universities -- Faculty -- Fiction; England -- Fiction; Italy -- Fiction